Isolated central nervous system relapses in primary mediastinal large B‐cell lymphoma after CHOP‐like chemotherapy with or without Rituximab. Issue 1 (18th May 2012) - Papageorgiou, Sotirios G.; Diamantopoulos, Panayiotis; Levidou, Georgia; Angelopoulou, Maria K.; Economopoulou, Panagiota; Efthimiou, Anna; Constantinou, Nikos; Katsigiannis, Andreas; Korkolopoulou, Penelope; Pappa, Vassiliki; Economopoulou, Christina; Georgiou, George; et al.
Abstract Central nervous system (CNS) involvement in patients with primary mediastinal large B‐cell (PMLBCL) lymphoma is a rare event, occurring in approximately 6% of patients, on the basis of the review of the literature prior to induction of Rituximab. The aim of this retrospective study was to describe the incidence of CNS relapse among 100 consecutive patients with PMLBCL who were treated with R‐CHOP ± RT in comparison to patients treated with CHOP ± RT (n = 45) in 11 hospitals in Greece. Two patients experienced a CNS relapse, representing an overall frequency of 2.0% in R‐CHOP treated patients and a 2‐year actuarial incidence of 2.3%. Both patients had isolated CNS relapses. The incidence of CNS relapse after CHOP without Rituximab was 2/45 (4.4%) for a 2‐year actuarial incidence of 7.5% (p = 0.29). Again, both patients had isolated CNS relapses. Parenchymal‐only localizations accounted for 3/4 cases. Risk factors for CNS involvement could include leukocytosis, poor performance status and higher age‐adjusted International Prognostic Index, although their impact was weakened by competing risk survival analysis. Both patients relapsing after R‐CHOP required CNS radiotherapy to achieve a complete remission and be forwarded to high‐dose therapy and autologous stem cell transplantation: They are both alive and disease‐free 18 and 23 months after CNS relapse. Both cases relapsing after CHOP without Rituximab were salvaged by CNS radiotherapy (one also received intrathecal chemotherapy) entering long‐term remissions. In conclusion, CNS relapses are rare in PMLBCL tending to be isolated in the CNS, probably reflecting the persistence of latent CNS disease than dissemination of resistant disease. The impact of Rituximab in reducing CNS relapses remains unknown. Established risk factors for CNS involvement in aggressive lymphomas may not be helpful in assessing the risk of CNS recurrence in this disease. Routine CNS prophylaxis is not probably required in PMLBCL. Copyright © 2012 John Wiley & Sons, Ltd.